Complex health problems in the oldest old in Sweden 1992–2002 - Meinow, Bettina (Eur J Ageing, 2006)
Most studies on health trends in the elderly population focus on specific conditions, studied one at a time. However, health problems are often interrelated and exist simultaneously in late life. Individuals with health problems in several domains present special challenges to care services. To estimate future needs for care it may be relevant to study trends of complex health problems as well as single health items. This study identified serious problems in three domains (diseases/symptoms, mobility, cognition/communication) in two representative samples of the Swedish population aged 77 and older (1992: n=537; 2002: n=561). People with serious problems in two or three domains were considered to have complex health problems. Changes between 1992 and 2002 in the prevalence of persons having serious problems in no, one and two/three domains were analyzed with logistic regressions. When examining each domain separately all three showed a significant increase of serious problems. For diseases/symptoms the increase remained significant after controlling for different age and gender distributions in the two surveys. Results showed a significant increase in the prevalence of having problems in one domain, as well as having problems in two or three domains (complex problems). Results persisted when adjusting for different distributions in age, gender and education between 1992 and 2002. Results suggest a worsening of health during the 10-year period and an increase of complex problems. This emphasizes the necessity of cooperation and collaboration between different kinds of medical and social services for elderly people.